Penyuluhan Peningkatan SDM Pariwisata pada Wisata Alam Pamah di Desa Telagah, Kecamatan Sei Binge, Kabupaten Langkat - Apriliani Lase; Mery Moy Mita; Angelia Putriana; Sabam Syahputra Manurung; Siti Aisyah (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2023)
The research aims to improve tourism human resources, develop the potential of tourist objects in the packaging of various tour packages, and create an information/direction system at the Pamah Alam tourist attraction. The development of tourism does not only occur in urban areas but can also occur in tourist areas. The tourist village is one of the alternative destinations in the field of tourism. Telagah tourist village has natural and cultural potential to be developed into an agro-tourism object and attraction that the local government and tourists recognize. Developing the tourism sector is one way to encourage productive economic growth. The potential possessed by Pamah natural attractions has beautiful natural scenery, fertile soil, and abundant natural wealth. Tourism management and proper use of nature is the biggest source of economic improvement for citizens. However, improvements are still needed in various fields, including human resources and the processing of Pamah Simelir crops to produce products with high selling value. The result of the implementation of community service is that participants can apply the knowledge gained in counseling and are given guidance to make tour packages and information signs (sign systems). Programs made by participants during the training process demonstrate good competence in understanding tourist attractions, locations, times, and routes.